A Ni(OH)2–PtO2 hybrid nanosheet array with ultralow Pt loading toward efficient and durable alkaline hydrogen evolution. Issue 5 (16th January 2018) - Xie, Lisi; Ren, Xiang; Liu, Qin; Cui, Guanwei; Ge, Ruixiang; Asiri, Abdullah M.; Sun, Xuping; Zhang, Qiuju; Chen, Liang
Abstract : The ultralow-Pt-content (Pt content: 5.1 wt%) Ni(OH)2 –PtO2 hybrid nanoarray behaves as a superb and durable electrocatalyst for alkaline hydrogen evolution. Abstract : The design and development of highly active electrocatalysts for the hydrogen evolution reaction (HER) in alkaline media is of significant importance. In this communication, we report the direct growth of an ultralow-Pt-content (Pt content: 5.1 wt%) Ni(OH)2 –PtO2 hybrid nanosheet array on a Ti mesh (Ni(OH)2 –PtO2 NS/Ti), carried out by hydrothermal treatment of a Ni(OH)2 nanosheet array on a Ti mesh (Ni(OH)2 NS/Ti) in the presence of [PtCl6 ] 2− . When used as a 3D catalyst electrode for the HER, the resulting Ni(OH)2 –PtO2 NS/Ti exhibits superior activity with the need of an overpotential of only 31.4 mV to deliver a geometrical catalytic current density of 4 mA cm −2 in 0.1 M KOH. Remarkably, this catalyst also shows strong long-term electrochemical durability for at least 100 h with a faradaic efficiency close to 100%. Density functional theory calculations reveal that the Ni(OH)2 /PtO2 interface can promote the kinetics of H2 O dissociation and tune the hydrogen adsorption free energy to a more moderate value, thereby promoting the HER.